Flexibilidad cognitiva en los estudiantes del Colegio “Chambo”. Chambo. Octubre 2017 –Marzo del 2018 - Parra Hidalgo, Daniel Alexander (2018)
This research project was designed to investigate the level of cognitive flexibility development in students in the third year of senior high school, Riobamba October 2017 - March 2018, determine the level of cognitive flexibility development in students and analyse it. The beneficiaries of the present investigation are the Chambo high school student to which the cognitive flexibility development research instruments were applied, to the students and future professionals of the Educational Psychology and all those who wish to know about the Cognitive Flexibility , methodologically this research has a qualitative approach since it has a social nature; it is non-experimental design since the variables were not intentionally manipulated; the research is bibliographic type because basically we took information from the source or references; the field since it was worked in the educational institution, cross-sectional because it was carried out in a determined time, the level of the investigation is descriptive, the technique used, was a psychometric test and the Color Test, Stroop Words as instruments. Ph D. Charles J. Golden, helped us to interpret and analyse the results, it allowed us to conclude that the cognitive flexibility development in those students, had a medium level.